Co application of biofertilizer and zinc oxide nanoparticles upregulate protective mechanism culminating improved arsenic resistance in maize. (May 2022) - Khan, Muhammad Ali; Yasmin, Humaira; Shah, Zafar Abbas; Rinklebe, Jörg; Alyemeni, Mohammed Nasser; Ahmad, Parvaiz
Abstract: During this study, the bioremediation potential of zinc-oxide nanoparticles (ZnO-NPs) and PGPR mixed biofertilizer (BF) on maize plants under induced arsenic (As) stress of 50 ppm and 100 ppm was investigated. The treated plants showed increased As resistance to mitigate the adverse effects of stress by enhancing fresh and dry biomass, relative water content, protein content, soluble sugars, proline content, enzymatic antioxidant defense mechanisms including activities of catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), superoxide dismutase (SOD), and malondialdehyde (MDA) content. In the pot experiment, the parameters studied have shown that the integrated treatments of ZnO-NPs and BF cause a notable enhancement in relative water content 43%–50% and plant biomass. Moreover, the same treatment showed a marked upregulation in enzymes activity (APX, SOD, APX, and CAT) which oxidized the cell-damaging ROS, produced in response to As stress. Likewise, the combined treatment showed a maximum reduction in MDA content 46%–57% and electrolyte leakage in As treated plants as compared to stressed plants. On the other hand, total soluble sugar 114%–170% and total protein content 117%–241% escalated. SEM analysis revealed marked damage reduction in the treated cells caused by arsenic toxicity. Thus, the use of BF comprised of rhizobacteria along with ZnO-NPs could be a very effective bio source for improving maize plant growth under As stress. In in silico study, As mediated network of proteins showed positive and negative regulation of As activity that leads to stress generation for housekeeping genome. Graphical abstract: Image 1 Highlights: Arsenic (As) concentration greater that 50 mg/kg in soil is vulnerable for maize. PGPRs containing biofertilizer (BF) could promote maize growth and reduces As uptake. Foliar spray of zinc oxide nanoparticles (ZnO-NPs) improves As tolerance in maize. Synergistic effects of both treatments showed reduced As uptake by As affected plants. Coapplication of BF and ZnO-NPs are more effective in decreasing As toxicity in maize.